Denny Sumargo's Podcast As A Source Of Information Social Issues From The Audience's Perspective - Azhira Zahranisa; Siti Khumayah; Aghnia Dian Lestari (Indonesian Journal Publisher, 2026)
The development of new media has driven changes in how people access information, including their understanding of social issues. The emergence of new media in the form of podcasts broadcast via YouTube has become a widely used medium, including Denny Sumargo’s podcast. This study aims to describe listeners’ perspectives on Denny Sumargo’s podcast as a medium for social issues, explain the motives behind their choice of this podcast, and analyze their post-listening experiences based on the Uses and Gratifications theory. The study employs a descriptive qualitative approach using in-depth interviews with five informants and observations of YouTube viewer comments. The results indicate that the Denny Sumargo Podcast is viewed as an information medium that presents social issues in depth. Listeners’ motivations include cognitive, affective, personal integration, social integration, and tension relief needs. Listeners’ experiences are informative, emotional, and reflective, and they foster social awareness and discussion. This study affirms the role of podcasts as a new medium in shaping understanding of social issues in the digital space.